The Wiley handbook of developmental psychopathology - Centifanti, Luna C. 1974-; Williams, David M. 1980- (Wiley Blackwell, 2017)
The Wiley Handbook of Developmental Psychopathology offers a concise, up-to-date, and international overview of the study of developmental psychopathology.